'It's the same thing as giving them CPR training': rural first responders' perspectives on naloxone - Matthew R. Filteau; Brandn Green; Frances Kim; Ki-Ai McBride (BMC, 2022)
Abstract The Substance Abuse and Mental Health Services Administration's (SAMHSA) Harm Reduction grant program expanded access to several harm reduction strategies to mitigate opioid overdose fatalities, including expanding access to naloxone. Interviews with first responders in a frontier and remote (FAR) state were conducted to understand their job responsibilities in relation to overdose response and prevention and their perceptions of training laypersons to administer naloxone. This study includes 22 interviews with law enforcement, EMS and/or fire personnel, and members of harm reduction-focused community organizations. The study finds widespread support for increasing access to naloxone and training laypersons in naloxone administration throughout Montana, due to rural first responders' inability to meet the needs of residents and an overall lack of resources to address addiction and the effects of fentanyl. Participants from harm reduction-focused community organizations convey support for training lay persons, but also illuminate that real and perceived cultural opposition to harm reduction strategies could reduce the likelihood that laypeople enroll in naloxone training. This study adds to the literature because it focuses on first responders in a FAR area that would benefit from layperson naloxone education and administration training due to its geographic expansiveness and the area's overall lack of access to medications for opioid use disorder or other treatment services. Expanding harm reduction approaches, like increasing access and training laypersons to administer naloxone, might be FAR residents' best chance for surviving an opioid overdose.